907 Overcoming the legacy of occupational lung diseases in mineworkers in southern africa – health services and compensation. (24th April 2018) - Kistnasamy, Barry; Fourie, Andre; Yu, Jessica; Yassi, Annalee
Abstract : Introduction: The mining sector that has driven the South African economy for over 100 years left a legacy of occupational lung diseases in mineworkers, their families and communities in Southern Africa not comparable with any other working populations and compounded by the migrant labour system. The 33 000 mineworkers compensated for silicosis, 109 000 for tuberculosis and 14 000 for asbestos-related disease amongst other occupational lung diseases over the past 30 years is thought to be only the tip of the iceberg. This study aimed to document progress towards ameliorating this situation and identifying residual challenges. Methods: A review was conducted of relevant policy and legislation and epidemiological studies showing the size, shape and scope of occupational lung diseases and access of current and ex-mineworkers to prevention interventions, health services and compensation. This was supplemented by 12 semi-structured interviews and data analysis. Result: The approach to the occupational lung disease challenges within the Southern African mining sector included the development of a database of 600 000 files, outreach services including fixed and mobile health units and financial services, tracking and tracing ex-mineworkers using geospatial mapping tools and increased compensation payments. Multi-stakeholder participation involving governments in the Southern Africa region, trade unions, the Chamber of Mines, ex-mineworker associations and multi-lateral agencies assisted with financial, infrastructural and technical resources. Discussion: The challenges in the post-apartheid era have meant that vast numbers of mineworkers who have fallen ill or became disabled as they worked to produce South Africa's mineral wealth were not receiving health services and compensation. Progress is now being made to address the problems identified. Despite these efforts there are barriers to access services including socio-cultural factors, distance and lack of knowledge amongst ex-mineworkers about occupational lung diseases and compensation.